Whey protein fractionation based on sp-sepharose cation exchange chromatography - Hazman, Abd Mulok (2010)
Bovine whey protein consists of different type of proteins such as βlactoglobulin (β-lag), α-lactalbumin (α-lac), immunoglobulin, bovine serum albumin (BSA), lactoferrin, lactoperoxidase and glycomacropeptide. Single protein is more valuable compare to the mixture of proteins and it can be used for specific application. The main objective of this study is to fractionate whey protein components into several groups or single protein fraction using SP-sepharose TM Fast Flow (Amersham Biosciences) cation exchange chromatography column. The chromatographic process was run at different pH range from pH 4 to pH 8 using 24 ml column. All major whey proteins were recovered in the elution fraction at pH 4 and pH 4.5. No protein was bound at pH 7 and pH 8. The best whey fractionation from 2 ml whey feed was achieved at pH 4 with the yield for β-lag, BSA and α-lac are 83.33%, 66.44% and 10.51% respectively. Different protein fraction recovered during fractionation process at different pH using cation exchange chromatography process, can be used as a guideline to isolate particular protein of interest from bovine whey